Liberia : Request for an Extension of the Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report, 2012)
This paper presents Liberia's request for an extension of the arrangement under the Extended Credit Facility (ECF). In December 2011, the Executive Board completed the seventh review under the ECF arrangement for Liberia. All performance criteria under the program through end-June 2011 have been observed, although completion of two structural benchmarks faced delays owing to limited implementation capacity and technical factors. Preliminary data for end-December 2011 indicate that performance criteria for net foreign exchange reserves, government borrowing, and revenues have been observed with significant margins.